2022
DOI: 10.1002/ece3.9409
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogeography of two commensal rat species (Rattus tanezumi and Rattus norvegicus) in China: Insights from mitochondrial DNA, microsatellite, and 2b‐RAD data

Abstract: Rattus norvegicus and Rattus tanezumi are dominant species of Chinese house rats, but the colonization and demographic history of two species in China have not been thoroughly explored. Phylogenetic analyses with mitochondrial DNA including 486 individuals from 31 localities revealed that R. norvegicus is widely distributed in China, R. tanezumi is mainly distributed in southern China with currently invading northward; northeast Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Moreover, the extensive construction of roads and bridges in recent decades likely facilitated the spread of commensal rats in China, as human-assisted dispersal can overcome environmental barriers ( Combs et al 2018 ). We observed that the CD samples displayed admixture of the South and Tibetan populations, which could be attributed to the Chuan-Zang highway linking Tibetan and Central China, which starts in CD and extends to Lhasa in Tibet ( Guo et al 2019 ; Jing et al 2022 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the extensive construction of roads and bridges in recent decades likely facilitated the spread of commensal rats in China, as human-assisted dispersal can overcome environmental barriers ( Combs et al 2018 ). We observed that the CD samples displayed admixture of the South and Tibetan populations, which could be attributed to the Chuan-Zang highway linking Tibetan and Central China, which starts in CD and extends to Lhasa in Tibet ( Guo et al 2019 ; Jing et al 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…It is the latest to undergo range expansion or invasion among the three species ( Bastos et al 2011 ; Lack et al 2012 ; Conroy et al 2013 ; Guo et al 2019 ; Liu et al 2021 ; Chen et al 2021a ). In the past 40 years, RT rats in southern China (below 30°N) have rapidly colonized regions below 40°N in the north, northwest, and Tibetan Plateau areas in China ( Shou 1962 ; Wilson and Reeder 2005 ; Guo et al 2019 ; Liu et al 2021 ; Chen et al 2021a ; Jing et al 2022 ). The recently introduced RT rats have partially replaced local RN rats due to their superior interspecific interference and high resistance to rodenticides, which has led them to outcompete RN rats ( Teng et al 2016 ; Guo et al 2017 ; Chen et al 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/genes14071442/s1, Table S1: Systematic review-final studies included [6,[19][20][21][28][29][30][31][35][36][37][38][39][41][42][43][44][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Supplementary Materialsmentioning
confidence: 99%